2016
DOI: 10.5433/2236-6407.2016v7n2p64
|View full text |Cite
|
Sign up to set email alerts
|

Adoecimento mental em professores brasileiros: revisão sistemática da literatura

Abstract: A saúde do professor é um tema que adquire crescente relevância científica, pois tal profissão é considerada como uma das mais estressantes. A presente revisão sistemática da literatura analisou produções científicas nacionais publicadas entre 2010 e 2015, com vista a identificar principais sintomas e/ou adoecimentos psíquicos entre professores brasileiros. Recorreu-se às bases LILACS, SciELO, Index Psicologia, Educ@ e PePSIC. Os critérios de elegibilidade e análise seguiram as diretrizes do PRISMA. Dos 97 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
70

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 37 publications
1
33
1
70
Order By: Relevance
“…The most important objective of this study was to assess the impact of Perceived Social and Organizational Support as well as socio-demographic aspects(age, time of service for teaching institutions, and weekly workload) over the incidence of Burnout Sydrome (BS) on university teachers from the private education system of a city in the Triângulo Mineiro, a region in the Brazilian state of Minas Gerais. According to Diehl and Marin (2016),"the teaching occupation is considered by the International Labor Organization (ILO) as one of the most stressful in the world. Teaching has become an exhausting activity with obvious repercussions on an individual's professional performance as well as on mental and physical health" (p. 65).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important objective of this study was to assess the impact of Perceived Social and Organizational Support as well as socio-demographic aspects(age, time of service for teaching institutions, and weekly workload) over the incidence of Burnout Sydrome (BS) on university teachers from the private education system of a city in the Triângulo Mineiro, a region in the Brazilian state of Minas Gerais. According to Diehl and Marin (2016),"the teaching occupation is considered by the International Labor Organization (ILO) as one of the most stressful in the world. Teaching has become an exhausting activity with obvious repercussions on an individual's professional performance as well as on mental and physical health" (p. 65).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that perceived organizational and social support for professionals is not listed by these authors. Diehl and Marin (2016), while revising the national production of studies on Burnout among Brazilian teachers in all levels of education in the 2010 to 2015 period, identified investigations on the quality of life of teachers as well as the most frequent occurrences among these professionals. The scope of studied variables focused on the symptoms because of a preoccupation to establish prevention measures for the benefit of these workers' health.…”
Section: Introductionmentioning
confidence: 99%
“…An adverse work context is a risk factor for the onset of depressive symptoms in teachers (Silva & Guillo, 2015;Diehl & Marin, 2016;Miranda, 2017). The prevalence of this symptomatology can reach 23% in this population (Silva, Bolsoni-Silva, & Loureiro, 2018), jeopardizing the successful performance of work activities (Serafim & Saffi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies dedicated to analyze the issue of the mental health of teachers stress the high emotional burden and psychic suffering that these professionals face 20,21,22 . The best known may be those that address the theme from the perspective of burnout syndrome 11,23 .…”
Section: Resultsmentioning
confidence: 99%